The Evolving Paradigm of Acne Vulgaris Management: A Systematic Review Emphasizing Evidence-Based Combination Therapy, Antimicrobial Stewardship, and Patient-Reported Outcomes - Cici Wulandari; Winda Sari; Sherli Wahyuni (International Medical Journal Corp. Ltd, 2025)
Introduction: Acne vulgaris (AV) is a highly prevalent, chronic inflammatory dermatosis that necessitates sophisticated, long-term management strategies to optimize physical clearance, minimize permanent scarring, and address the substantial psychosocial impact on patients.1 This systematic review aimed to critically synthesize recent, high-certainty evidence informing the comparative efficacy, safety, and durability of therapeutic interventions for AV, specifically focusing on the public health imperative of antimicrobial stewardship and the mandatory utilization of patient-reported outcomes (PROs).2 Methods: We conducted a systematic search for randomized controlled trials (RCTs) and systematic reviews published in major databases up to the current date, adhering to the PRISMA 2020 guidelines.4 Inclusion criteria focused on studies addressing treatment efficacy (topical combinations, systemic antibiotics, hormonal therapy, oral retinoids, and physical modalities) for patients aged 9 years and older.3 Methodological quality was assessed using the Cochrane Risk of Bias (RoB 2.0) tool.6 We prioritized the synthesis of ten distinct outcomes, including lesion count reduction (LCR), Investigator Global Assessment (IGA) success, discontinuation rates, specific adverse events (AEs), durability (relapse rates), and changes in the Dermatology Life Quality Index (DLQI).2 Results: Data were synthesized from 17 representative studies or data analyses. Topical combination therapies were significantly superior to monotherapy, with fixed-dose Adapalene 0.3%/Benzoyl Peroxide 2.5% achieving a 68.7% reduction in inflammatory lesions and a 68.3% reduction in non-inflammatory lesions by week 12.7 For systemic management, Spironolactone demonstrated robust objective efficacy in adult women, showing a sixfold increase in the odds of treatment success compared to placebo (Odds Ratio (OR) 6.59; 95% CI 3.50–12.43), a finding validated by Trial Sequential Analysis.6 Conversely, temporal analysis revealed a significant positive correlation (R=0.69) between time and rising C. acnes resistance to Erythromycin, escalating from 10% in 2008 to 44% in 2024, highlighting a critical failure of antimicrobial stewardship.8 Furthermore, a statistically moderate correlation was observed between physician-assessed IGA improvement and patient-reported QoL improvement (DLQI) (r=0.516, P < 0.001), suggesting a significant discrepancy in current success metrics.2 Physical modalities were primarily characterized by a high overall risk of bias due to lack of blinding.9 Discussion: The evidence mandates a paradigm shift toward non-antibiotic systemic interventions and combination therapy as the first-line standard for all disease severities. The demonstrated high certainty of Spironolactone efficacy 6 makes it the preferred systemic agent for adult female AV, mitigating the public health crisis of antimicrobial resistance fueled by historical over-prescription.8 The weak correlation between IGA and DLQI necessitates the routine incorporation of PROs as primary endpoints in future trials to accurately capture therapeutic benefit from the patient's perspective.2 Conclusion: Effective, safe, and durable AV management relies on the early and mandatory use of combinations of topical retinoids and Benzoyl Peroxide, strict limitation of systemic antibiotic duration, and aggressive utilization of non-antibiotic systemic agents. Future clinical research must focus on validating physical modalities through low-bias RCTs and standardizing QoL metrics as core outcome measures.